The burden of atopic dermatitis in Portuguese patients - Coelho, Pedro Simões (2024)
Coelho, P. S., Apalhão, M., Victorino, G., Cardoso, C., Camilo, J., & Silva, J. M. (2024). The burden of atopic dermatitis in Portuguese patients: an observational study. Scientific Reports, 14, 1-8. Article 5181. https://doi.org/10.1038/s41598-024-55965-y --- The study was conducted with the support of NOVA IMS, SPDV and ADERMAP and was funded by Sanofi